An Integrative Approach to Presence and Self-Motion Perception Research - Riecke, Bernhard E.; Schulte-Pelkum, Jörg (Immersed in Media: Telepresence Theory, Measurement and Technology, 2015)
This chapter is concerned with the perception and simulation of self-motion in virtual environments, and how spatial presence and other higher cognitive and top-down factors can contribute to improve the illusion of self-motion (“vection”) in virtual reality (VR). In the real world, we are used to being able to move around freely and interact with our environment in a natural and effortless manner. Current VR technology does, however, hardly allow for natural, life-like interaction between the user and the virtual environment. One crucial shortcoming is the insufficient and often unconvincing simulation of self-motion, which frequently causes disorientation, unease, and motion sickness. The specific focus of this chapter is the investigation of potential relations between higher-level factors like presence on the one hand and self-motion perception in VR on the other hand. Even though both presence and self-motion illusions have been extensively studied in the past, the question whether/how they might be linked to one another has received relatively little attention by researchers so far. After reviewing relevant literature on vection and presence, we present data from two experiments, which explicitly investigated potential relations between vection and presence and indicate that there might indeed be a direct link between these two phenomena. We discuss theoretical and practical implications from these findings and conclude by sketching a tentative theoretical framework that discusses how a broadened view that incorporates both presence and vection research might lead to a better understanding of both phenomena, and might ultimately be employed to improve not only the perceptual effectiveness of a given VR simulation, but also its behavioural and goal/application-specific effectiveness.
Keywords: Biomedical Engineering; Cognition; Computer Imaging, Vision, Pattern Recognition and Graphics; Control, Robotics, Mechatronics; DG2019; NSERC DG 2026; Riecke; Riecke_2015; Vection; Virtual environments; Walking; joerg-schulte-pelkum; locomotion; motion simulation; multi-modal vection; review; vection; vection review; virtual reality